Method for manufacturing substrate with conductive via and method for manufacturing wiring substrate with conductive via

By using metal paste of metal particles and volatile solvents, a planar conductive via precursor is formed and fired, and the problems of long copper plating process and substrate rupture in the prior art are solved, thereby achieving efficient and simple conduction with electricity Through-hole substrate manufacturing and wiring connection.

CN119156892APending Publication Date: 2024-12-17RESONAC CORP
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202480002342.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-03-15
Filing Date
2024-02-27
Publication Date
2024-12-17

AI Technical Summary

Technical Problem

In the prior art, when manufacturing a substrate with conductive via holes, the copper plating process needs to suppress the precipitation speed of the copper cover film, resulting in a longer working time, and the chemical mechanical polishing process reduces productivity or causes the substrate to rupture.

Method used

Using a metal paste containing metal particles and a volatile solvent, the volatile solvent is removed by heating to form a planar conductive via precursor, and a conductive via is formed by firing, the CMP process is omitted, and the process flow is simplified.

Benefits of technology

It is possible to easily obtain a conductive through-hole substrate with sufficient flatness, improve production efficiency, avoid the risk of substrate breakage, and form efficient wiring through conductive through-hole connection.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005104902880000241
    Figure BDA0005104902880000241
  • Figure BDA0005104902880000251
    Figure BDA0005104902880000251
  • Figure BDA0005104902880000261
    Figure BDA0005104902880000261
Patent Text Reader

Abstract

A method for manufacturing a substrate with a conductive through hole, the method comprising: a step a for preparing a substrate provided with a hole, and providing a metal paste part containing metal particles and a volatile solvent so as to fill the inside of the hole and cover at least the surface of the periphery of the hole of the substrate; a step b in which the metal paste part is heated so as to remove a portion of the volatile solvent; a step c in which a portion of the heated metal paste portion is removed so as to expose the surface, and a conductive via precursor having a planarized exposed surface and containing the remainder of the metal particles and the volatile solvent is formed inside the hole; and a step d in which the conductive via precursor is fired to form a conductive via.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a method for manufacturing a substrate with conductive through holes and a method for manufacturing a wiring substrate with conductive through holes. Background Art

[0002] In recent years, in order to miniaturize, improve functionality and integrate electronic devices or parts, three-dimensional mounting technology has attracted much attention. In the three-dimensional mounting technology, upper and lower silicon substrates are electrically connected on the silicon substrate via electrodes called through silicon vias (TSV: Through Silicon Via), and semiconductor chips are stacked at a high density in the vertical direction (height direction).

[0003] As a method for forming a through silicon via, for example, Patent Document 1 discloses a method for manufacturing a semiconductor device having a through silicon via, which includes a step of copper-plating a non-through hole formed in a silicon substrate by electroplating using a specific copper plating solution.

[0004] Previous technical literature

[0005] Patent Literature

[0006] Patent Document 1: Japanese Patent Application Publication No. 2019-16712 Summary of the invention

[0007] Technical issues to be solved by the invention

[0008] However, the above method needs to perform plating while suppressing the precipitation rate of the copper film, so the operation time becomes long, and there is a problem in productivity. In addition, the flattening is performed by CMP (Chemical Mechanical Polishing) for multilayering, but if there is a CMP process, there are disadvantages such as reduced productivity due to the time required for polishing, or the substrate may be cracked due to polishing.

[0009] Therefore, an object of the present invention is to provide a method for manufacturing a substrate with conductive vias that can easily obtain a substrate with conductive vias having sufficient flatness. Also, an object of the present invention is to provide a method for manufacturing a wiring substrate with conductive vias that can easily obtain a wiring substrate with conductive vias having wiring connected through conductive vias.

[0010] Means for solving technical problems

[0011] In order to solve the above-mentioned problems, one aspect of the present invention provides the following method for manufacturing a substrate with conductive vias and a method for manufacturing a wiring substrate with conductive vias.

[0012] [1] A method for manufacturing a substrate with a conductive via, comprising: step a, preparing a substrate with a hole, providing a metal paste portion in a manner that fills the inside of the hole and covers the surface of the substrate at least around the hole, wherein the metal paste portion contains metal particles and a volatile solvent; step b, heating the metal paste portion to remove a portion of the volatile solvent; step c, removing a portion of the heated metal paste portion in a manner that exposes the surface to form a conductive via precursor having a flattened exposed surface inside the hole and containing the metal particles and the remaining portion of the volatile solvent; and step d, sintering the conductive via precursor.

[0013] [2] The method according to the above [1], wherein the concentration of metal particles in the metal paste portion provided in the step a is greater than 94 mass %, and in the step b, the metal paste portion is heated in such a manner that the concentration of metal particles becomes greater than 97.5 mass %.

[0014] [3] The method according to [1] or [2] above, wherein the volatile solvent contains a high vapor pressure solvent having a vapor pressure of 4 Pa ​​to 30 Pa at 20°C, and the heating temperature in step b is less than 100°C.

[0015] [4] A method according to any one of [1] to [3] above, wherein in step a, a metal particle film having a support film and a metal particle-containing layer disposed on the support film and comprising the metal particles and the volatile solvent is prepared, and the metal particle-containing layer of the metal particle film is pressed against the substrate to provide the metal paste portion.

[0016] [5] A method for producing a wiring substrate with conductive vias, comprising the step of forming wiring on the substrate with conductive vias obtained by the method described in any one of [1] to [4] above.

[0017] Effects of the Invention

[0018] According to the present invention, a substrate with conductive vias having sufficient flatness can be easily obtained. That is, according to the method described in [1] above, after providing a metal paste portion containing metal particles and a volatile solvent in step a, through steps b and c, it is possible to take into account both good filling of the interior of the hole and formation of a conductive via precursor that is unlikely to shrink in volume by firing, and to align the substrate surface with the exposed surface of the conductive via precursor, and through step d, the height difference with the substrate surface can be sufficiently reduced to form a conductive via. Thus, a substrate with conductive vias having sufficient flatness can be easily obtained, and a planarization step such as a CMP step can be omitted.

[0019] Furthermore, according to the present invention, a wiring board with conductive vias having wiring connected by conductive vias can be easily obtained. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 It is a schematic diagram showing an example of a method for manufacturing a substrate with conductive vias according to the present embodiment.

[0021] Figure 2 It is a schematic diagram showing an example of a method for manufacturing a substrate with conductive vias according to the present embodiment.

[0022] Figure 3 It is a schematic diagram showing an example of a method for manufacturing a substrate with conductive vias according to the present embodiment.

[0023] Figure 4 It is a schematic diagram showing an example of a method for manufacturing a wiring board with conductive vias according to the present embodiment.

[0024] Figure 5 It is a schematic diagram showing a test piece.

[0025] Figure 6 This is a cross-sectional photograph of a conductive through hole in the silicon substrate with a conductive through hole produced in Example 1.

[0026] Figure 7 is a cross-sectional photograph of a conductive via in the sample produced in Example 1. DETAILED DESCRIPTION

[0027] Hereinafter, the mode for implementing the present invention will be described in detail with reference to the accompanying drawings. The present invention is not limited to the following embodiments. In addition, in the accompanying drawings, the same or corresponding parts are marked with the same symbols, and repeated descriptions are omitted.

[0028] <Method for manufacturing substrate with conductive through-hole>

[0029] The manufacturing method of a substrate with a conductive via of the present embodiment includes: step a, preparing a substrate with a hole, and providing a metal paste portion in a manner to fill the inside of the hole and cover the surface of at least the periphery of the hole of the substrate, wherein the metal paste portion contains metal particles and a volatile solvent; step b, heating the metal paste portion to remove a portion of the volatile solvent; step c, removing a portion of the heated metal paste portion in a manner to expose the above-mentioned surface to form a conductive via precursor having a flattened exposed surface and containing the remaining portion of the metal particles and the volatile solvent inside the hole; and step d, sintering the conductive via precursor to form a conductive via.

[0030] Figure 1 to Figure 3Schematic diagram showing an example of a method for manufacturing a substrate with conductive vias according to the present embodiment. Figure 1 An example of a substrate used in the method for manufacturing a substrate with conductive vias is shown in . Hereinafter, the method for manufacturing a substrate with conductive vias according to the present embodiment will be described with reference to these figures.

[0031] [Process a]

[0032] As the substrate provided with holes prepared in this process, a silicon substrate, a glass substrate, a ceramic substrate, a printed circuit board, a semiconductor package substrate, etc. can be cited. The hole can be a through hole or a non-through hole. In this embodiment, for example, Figure 1 As shown in (a), a silicon substrate 40 can be prepared, which includes a silicon wafer 1 provided with a through hole 30 and a metal film 2 provided on the wall surface of the through hole and the surface of the silicon wafer 1. The through hole 30 extends to the two main surfaces of the silicon substrate 40. An example is given of a case where a conductive through hole is provided on the silicon substrate 40, but the following description may also replace the silicon wafer with other insulating substrates.

[0033] The thickness of the silicon wafer 1 can be greater than 100 μm, greater than 200 μm, or greater than 300 μm from the viewpoint of suppressing warping of the substrate after sintering, and can be less than 800 μm, less than 300 μm, less than 200 μm, or less than 100 μm from the viewpoint of lightweighting and increasing density of the substrate.

[0034] From the perspective of achieving high density of the obtained semiconductor device, the upper limit value of the aperture diameter of the through hole 30 can be less than 200 μm, less than 100 μm or less than 60 μm, and the lower limit value of the aperture diameter of the through hole 30 is not particularly limited, and can be greater than 20 μm, greater than 30 μm, or greater than 50 μm.

[0035] From the viewpoint of achieving high density of the obtained semiconductor device, the number of through holes 30 provided in the silicon substrate 40 is 1 cm per the main surface of the substrate. 2 , can be more than 100, more than 200 or more than 300.

[0036] The metal film 2 may be provided on both main surfaces of the silicon wafer 1 and the wall surface of the through hole 30, or may be provided on at least one main surface of the silicon wafer 1 and the wall surface of the through hole 30, or may be provided only on the wall surface of the through hole 30, or may not be provided. Figure 1 In the embodiment shown in (a), the silicon substrate 40 includes the metal film 2 on both main surfaces of the silicon wafer 1 and the wall surface of the through hole 30 .

[0037] As the metal film 2, for example, titanium, nickel, chromium, copper, aluminum, palladium, platinum and gold can be cited. From the viewpoint of adhesion, the metal film 2 is preferably a film obtained by sequentially forming titanium, nickel and copper into layers. The surface of the silicon wafer 1 is oxidized to form silicon oxide, and a titanium layer is formed on the silicon oxide to improve adhesion. In addition, by providing a nickel layer on the titanium layer and a copper layer thereon, it is possible to suppress the diffusion of copper into the silicon wafer 1 compared to the case where a copper layer is directly provided on the titanium layer. In addition, by providing a copper layer on the surface, the adhesion between the copper layer and the copper particles in the metal paste is improved, thereby improving reliability.

[0038] In addition, if Figure 1 As shown in (b), when a silicon substrate 41 having a non-through hole 31 as a hole is prepared, after step a, step b, step c or step d, the side of the silicon substrate opposite to the surface where the non-through hole 31 is opened is polished, thereby forming a conductive through hole as a through electrode. Examples of the polishing method include mechanical polishing and chemical mechanical polishing.

[0039] like Figure 2 (a)~ Figure 2 As shown in (c), the metal paste portion 3 can be provided, for example, by preparing a metal particle film having a metal particle-containing layer 3 p formed of a metal paste provided on a support film 7 and pressing the metal particle film against a substrate.

[0040] Examples of the support film 7 include polyimide films, polyethylene naphthalate films, and polyethylene terephthalate films. From the viewpoint of workability for forming the metal particle-containing layer by coating, the thickness of the support film may be 20 to 200 μm, 25 to 175 μm, or 30 to 150 μm.

[0041] (Metallic Paste)

[0042] The metal paste contains metal particles and a volatile solvent.

[0043] The concentration of the metal particles in the metal paste may be 92 mass % or more, 94 mass % or more, or 95 mass % or less, 98 mass % or less, 97 mass % or less, or 96 mass % or less.

[0044] Examples of metal particles include particles of nickel, silver, copper, gold, palladium, platinum, and solder. When the metal paste includes copper particles and solder particles, it is easy to obtain a conductor having sufficient conductivity and whose resistance value is not easily increased even when subjected to temperature changes, and a substrate having a through electrode having sufficient conductivity and excellent connection reliability. In this embodiment, the metal particles may include first copper particles having an average particle size of 0.8 μm or more, second copper particles having an average particle size of 0.4 μm or less, and solder particles.

[0045] In addition, in this specification, the average particle size of particles means the 50% volume average particle size (D50). When the volume average particle size of metal particles is determined, it can be determined by using a laser diffraction / scattering particle size distribution measuring apparatus to measure a substance obtained by dispersing metal particles as a raw material in a dispersion medium such as water or alcohol.

[0046] From the viewpoint of increasing the sintering density in the holes (e.g., through holes or non-through holes) of the substrate to suppress voids and cracks generated in the holes, the average particle size of the first copper particles may be 0.8 μm or more, 1.0 μm or more, 2.0 μm or more, or 3.0 μm or more. For example, from the viewpoint of suppressing the clogging of particles in micro-through holes with an inner diameter of 50 μm or less to improve the filling property, the average particle size of the first copper particles may be 10 μm or less, 8.0 μm or less, 5.0 μm or less, or 4.0 μm or less. From the viewpoint of suppressing voids and cracks and suppressing the clogging of particles in micro-through holes, the average particle size of the first copper particles may be 0.8 μm to 4.0 μm, 1.0 μm to 3.5 μm, or 1.2 μm to 3.0 μm.

[0047] The shape of the first copper particle can be, for example, spherical, blocky, needle-shaped, flat (sheet-shaped), roughly spherical, etc. The first copper particle can be an aggregate of copper particles having these shapes. From the perspective of reducing the height difference between the formed conductive through-hole portion and the substrate surface and suppressing the change in connection resistance even after a reliability test (e.g., a temperature cycle test), the metal paste of this embodiment can contain spherical copper particles as the first copper particles.

[0048] From the viewpoint of making the metal paste printable, the content of particles having an aspect ratio of 2 or less, such as spherical particles of the first copper particles, may be 60% by mass or more, 80% by mass or more, or 100% by mass. In addition, the aspect ratio (major axis / minor axis) of the particles can be obtained, for example, by observing an SEM image of the particles and measuring the major axis and the minor axis (e.g., thickness).

[0049] The first copper particles can be produced by a chemical reduction method, an atomization method, an electrolysis method, a pulverization method, a plasma rotating electrode method, a uniform droplet spray method, a heat treatment method, etc. From the viewpoint of easily obtaining a uniform diameter and improving the dispersibility of the metal paste, the first copper particles can be wet copper powder or atomized copper powder.

[0050] The first copper particle may include wet copper powder. In this case, a conductive through hole with excellent conductivity is easily obtained. This effect is believed to be obtained by the property that the wet copper powder is easily bonded to the second copper particle. The D90 / D50 of the wet copper powder may be 1.5 or less.

[0051] Furthermore, the first copper particle can contain wet copper powder and atomized copper powder. At this time, it is easy to improve the printability of the metal paste, and it is easy to reduce the height difference between the formed conductive through-hole portion and the surface of the substrate and suppress the change of the connection resistance even after the reliability test (for example, a temperature cycle test). As the reason why this effect can be obtained, it is speculated as follows. That is, it is believed that by making the wet copper powder that is easy to bond with the second copper particle and has a consistent particle size and the atomized copper powder with a wide particle size distribution coexist, the wet copper powder bonds the atomized copper powders and also bonds with the second copper particles, so that a firm sintered body can be formed through the densest filling structure, and the shrinkage during sintering can be suppressed to suppress the generation of voids or cracks and suppress depressions. The D90 / D50 of the atomized copper powder can be greater than 1.6, or greater than 1.7, or greater than 1.8.

[0052] When the first copper particles contain wet copper powder and atomized copper powder, the content of the wet copper powder may be greater than 0 mass part and less than 100 mass parts, or 20 to 80 mass parts, based on 100 mass parts of the total amount of the wet copper powder and the atomized copper powder.

[0053] As the first copper particles, commercially available products can be used. Examples of commercially available first copper particles include 1050Y (manufactured by Mitsui Mining & Smelting Co., Ltd., product name, average particle size (D50): 0.81 μm, D90: 1.1 μm, spherical, wet copper powder), 1100Y (manufactured by Mitsui Mining & Smelting Co., Ltd., product name, average particle size (D50): 1.1 μm, D90: 1.6 μm, spherical, wet copper powder), 1200Y (manufactured by Mitsui Mining & Smelting Co., Ltd., product name, average particle size (D50): 2.1 μm, D90: 3.1 μm, spherical, wet copper powder), 1300Y (manufactured by Mitsui Mining & Smelting Co., Ltd., product name, average particle size (D50): 2.1 μm, D90: 3.1 μm, spherical, wet copper powder), and 1400Y (manufactured by Mitsui Mining & Smelting Co., Ltd., product name, average particle size (D50): 2.1 μm, D90: 3.1 μm, spherical, wet copper powder). Mining & Smelting Co., Ltd., product name, average particle size (D50): 3.5μm, D90: 5μm, spherical, wet copper powder), 1100YP (Mitsui Mining & Smelting Co., Ltd., product name, average particle size (D50): 1.4μm, D90: 2.3μm, flat, wet copper powder), 1200YP (Mitsui Mining & Smelting Co., Ltd., product name, average particle size (D50): 3.1μm, D90: 5.3μm, flat, wet copper powder), MA-C02K (Mitsui Mining & Smelting Co., Ltd., product name, average particle size (D50): 1.8μm, D90: 3.6μm, spherical, atomized copper powder), MA-C025K (Mitsui Mining & Smelting Co., Ltd., product name, average particle size (D50): 2.4μm, D90: 5.2μm, spherical, atomized copper powder), MA-C03K (Mitsui Mining & Smelting Co., Ltd., product name, average particle size (D50): 3.4μm, D90: 6.3μm, spherical, atomized copper powder).

[0054] From the viewpoint of dispersion stability and oxidation resistance, the first copper particle can be treated by a surface treatment agent. The surface treatment agent can be removed when the wiring is formed (when the copper particles are sintered). As such a surface treatment agent, for example, aliphatic carboxylic acids such as palmitic acid, stearic acid, arachidic acid, and oleic acid; aromatic carboxylic acids such as terephthalic acid, pyromellitic acid, and o-phenoxybenzoic acid; aliphatic alcohols such as cetyl alcohol, stearyl alcohol, isobornyl cyclohexanol, and tetraethylene glycol; aromatic alcohols such as p-phenylphenol; alkylamines such as octylamine, dodecylamine, and stearylamine; aliphatic nitriles such as stearonitrile and decanoonitrile; silane coupling agents such as alkyl alkoxysilanes; polymer treatment agents such as polyethylene glycol, polyvinyl alcohol, polyvinyl pyrrolidone, and silicone oligomers, etc. The surface treatment agent can be used alone or in combination of two or more.

[0055] The treatment amount of the surface treatment agent can be an amount of one molecular layer or more on the particle surface. The treatment amount of the surface treatment agent varies according to the specific surface area of ​​the first copper particle, the molecular weight of the surface treatment agent, and the minimum coverage area of ​​the surface treatment agent. The treatment amount of the surface treatment agent is usually 0.001 mass % or more.

[0056] The treatment amount of the surface treatment agent can be determined based on the number of molecular layers (n) attached to the surface of the first copper particle, the specific surface area (A) of the first copper particle, and the surface area (B) of the first copper particle. p )(Unit: m 2 / g), molecular weight of the surface treatment agent (M s )(unit: g / mol), minimum coverage area of ​​surface treatment agent (S S )(Unit: m 2 / ), Avogadro constant (N A )(6.02×10 23 Specifically, the treatment amount of the surface treatment agent is calculated as follows: treatment amount of the surface treatment agent (mass %) = {(n×A p ×M s ) / (S S ×N A +n×A p ×M s )}×100% formula.

[0057] The specific surface area of ​​the first copper particle can be calculated by measuring the dried copper particle using the BET specific surface area measurement method. The minimum coverage area of ​​the surface treatment agent is 2.05×10 - 19 m 2 / 1 molecule. In the case of other surface treatment agents, for example, it can be determined by calculation based on a molecular model or by the method described in "Chemistry and Education" (Kamieda Jiebo, Inafuku Jun'o, Mori Yan, 40 (2), 1992, p114-117). An example of a quantitative method for a surface treatment agent is shown. The surface treatment agent can be identified by thermal desorption-gas chromatography-mass spectrometry of a dry powder after removing the dispersion medium from a metal paste, thereby determining the number of carbon atoms and the molecular weight of the surface treatment agent. The carbon component ratio of the surface treatment agent can be analyzed by carbon component analysis. As an example of a carbon component analysis method, a high-frequency induction heating furnace combustion-infrared absorption method can be cited. The surface treatment dosage can be calculated based on the carbon atom number, molecular weight and carbon component ratio of the identified surface treatment agent and by the above formula.

[0058] (Second copper particle)

[0059] From the viewpoint of sinterability, the average particle size of the second copper particles can be 0.4 μm or less, 0.3 μm or less, or 0.2 μm or less. From the viewpoints of suppressing synthesis costs, achieving good dispersibility, and suppressing the amount of surface treatment agent used, the average particle size of the second copper particles can be 0.01 μm or more, 0.03 μm or more, 0.05 μm or more, 0.08 μm or more, or 0.1 μm or more. From the viewpoint of obtaining sinterability at low temperatures and good dispersibility in the paste, the average particle size of the second copper particles can be 0.1 μm to 0.3 μm, 0.12 μm to 0.28 μm, or 0.15 μm to 0.25 μm.

[0060] The second copper particles can function as copper particles that well bond the first copper particles. Furthermore, the second copper particles have better sinterability than the first copper particles and can have a function of promoting the sintering of the copper particles. For example, compared with the case where the first copper particles are used alone as copper particles, the copper particles can be sintered at a lower temperature.

[0061] The second copper particles may be wet copper powder produced by a chemical reduction method.

[0062] The shape of the second copper particle can be, for example, spherical, blocky, needle-shaped, flat (sheet-shaped), roughly spherical, etc. The second copper particle can be an agglomerate of copper particles having these shapes. From the viewpoint of dispersibility and filling, the shape of the second copper particle can be spherical, roughly spherical, flat (sheet-shaped), and from the viewpoint of combustibility and miscibility with the first copper particle, the shape of the second copper particle can be spherical or roughly spherical.

[0063] The aspect ratio of the second copper particles may be 5 or less, 4 or less, or 3 or less from the viewpoint of dispersibility, filling property, and miscibility with the first copper particles.

[0064] As the second copper particles, synthetic copper particles or commercially available copper particles can be used. Examples of commercially available second copper particles include CH0200L1 (manufactured by Mitsui Mining & Smelting Co., Ltd., product name, average particle size (D50): 200 nm, spherical) and Tn-Cu100 (manufactured by TAIYO NIPPON SANSO CORPORATION, average particle size (D50): 120 nm, spherical).

[0065] The second copper particle can be treated with a specific surface treatment agent. As the specific surface treatment agent, for example, an organic acid having 8 to 16 carbon atoms can be mentioned. As the organic acid having 8 to 16 carbon atoms, for example, octanoic acid, methylheptanoic acid, ethylhexanoic acid, propylpentanoic acid, nonanoic acid, methyloctanoic acid, ethylheptanoic acid, propylhexanoic acid, decanoic acid, methylnonanoic acid, ethyloctanoic acid, propylheptanoic acid, butylhexanoic acid, undecanoic acid, methyldecanoic acid, ethylnonanoic acid, propyloctanoic acid, butylheptanoic acid, lauric acid, methylundecanoic acid, ethyldecanoic acid, propylnonanoic acid, butyloctanoic acid, pentylheptanoic acid, tridecanoic acid, methyldodecanoic acid, ethylundecanoic acid, propyldecanoic acid, butylnonanoic acid, pentyloctanoic acid, myristic acid, methyltridecanoic acid, ethyldodecanoic acid, propylundecanoic acid, butyldecanoic acid, pentylnonanoic acid, hexyloctanoic acid, pentadecanoic acid, methyltetradecanoic acid, ethyltridecanoic acid , propyl dodecanoic acid, butyl undecanoic acid, pentyl decanoic acid, hexyl nonanoic acid, palmitic acid, methyl pentadecanoic acid, ethyl tetradecanoic acid, propyl tridecanoic acid, butyl dodecanoic acid, pentyl undecanoic acid, hexyl decanoic acid, heptyl nonanoic acid, methyl cyclohexane carboxylic acid, ethyl cyclohexane carboxylic acid, propyl cyclohexane carboxylic acid, butyl cyclohexane carboxylic acid, pentyl cyclohexane carboxylic acid, hexyl cyclohexane carboxylic acid, heptyl cyclohexane carboxylic acid, octyl cyclohexane carboxylic acid, nonyl cyclohexane carboxylic acid and other saturated fatty acids; octenic acid, nonenic acid, methyl nonenic acid, decenoic acid, undecenoic acid, dodecenoic acid, tridecenoic acid, tetradecenoic acid, myristic acid, pentadecenoic acid, hexadecenoic acid, palmitic acid, cis-6-hexadecenoic acid (sapienic acid unsaturated fatty acids such as terephthalic acid, pyromellitic acid, o-phenoxybenzoic acid, methylbenzoic acid, ethylbenzoic acid, propylbenzoic acid, butylbenzoic acid, pentylbenzoic acid, hexylbenzoic acid, heptylbenzoic acid, octylbenzoic acid, nonylbenzoic acid, and other aromatic carboxylic acids. The organic acid may be used alone or in combination of two or more. There is a tendency that by combining such an organic acid with the second copper particle, both the dispersibility of the second copper particle and the release of the organic acid during sintering can be taken into account.

[0066] The treatment amount of the surface treatment agent can be an amount in which one to three molecular layers are attached to the surface of the second copper particle. The treatment amount of the surface treatment agent can be 0.07 mass % or more, 0.10 mass % or more, or 0.2 mass % or less, or 2.1 mass % or less, 1.6 mass % or less, or 1.1 mass % or less. The surface treatment amount of the second copper particle can be calculated by the method described for the first copper particle. The specific surface area, the molecular weight of the surface treatment agent, and the minimum coverage area of ​​the surface treatment agent are also the same.

[0067] When the total mass of the metal particles is 100 parts by mass, the total content of the first copper particles and the second copper particles in the metal paste may be 85 to 99.5 parts by mass, 90 to 99 parts by mass, or 95 to 98 parts by mass.

[0068] The contents of the first copper particles and the second copper particles may be 5 to 95 parts by mass and 95 to 5 parts by mass, 20 to 80 parts by mass and 80 to 20 parts by mass, or 30 to 70 parts by mass and 70 to 30 parts by mass, respectively, based on 100 parts by mass of the total of the first copper particles and the second copper particles.

[0069] (Solder particles)

[0070] Solder particles containing tin or a tin alloy can be used as solder particles. As tin alloys, for example, In-Sn, In-Sn-Ag, Sn-Bi, Sn-Bi-Ag, Sn-Ag-Cu, and Sn-Cu alloys can be used, and the following examples can be given.

[0071] In-Sn (In 52 mass%, Sn 48 mass%, melting point: 118°C)

[0072] In-Sn-Ag (In 20 mass%, Sn 77.2 mass%, Ag 2.8 mass%, melting point: 175°C)

[0073] Sn-Bi (Sn 43 mass%, Bi 57 mass%, melting point: 138°C)

[0074] Sn-Bi-Ag (Sn 42 mass%, Bi 57 mass%, Ag 1 mass%, melting point: 139°C)

[0075] Sn-Ag-Cu (Sn 96.5 mass%, Ag 3 mass%, Cu 0.5 mass%, melting point: 217°C)

[0076] Sn-Cu (Sn 99.3 mass%, Cu 0.7 mass%, melting point: 227°C)

[0077] From the viewpoint of suppressing volume shrinkage caused by sintering in the hole and suppressing the voids generated in the through-hole, the average particle size of the solder particles can be 1.0 μm or more, 1.5 μm or more, 2.0 μm or more, 3.0 μm or more, or 4.0 μm or more. From the viewpoint of making the distribution of the solder particles in the hole more uniform and reducing the size of the voids generated near the solder particles, the average particle size of the solder particles can be 15 μm or less, 10 μm or less, 8.0 μm or less, or 5.0 μm or less. From the viewpoint of suppressing volume shrinkage and improving the dispersibility of the solder particles so that the size of the voids is as small as possible and dispersed, the average particle size of the solder particles can be 2.0 μm to 8.0 μm, 2.5 μm to 7.0 μm, or 3.0 μm to 6.0 μm. By making the solder particles have such a particle size, the volume shrinkage of the conductive via precursor described later during sintering can be sufficiently reduced, and a conductive via portion having a porous structure and a sufficiently formed conductive network can be easily formed in the hole while reducing the height difference with the substrate surface. Thus, even after the wiring is formed, a sufficiently low connection resistance value can be displayed, and disconnection caused by thermal stress of the wiring can be further suppressed.

[0078] The shape of the solder particles may be, for example, spherical, blocky, needle-like, flat (flaky), or substantially spherical, etc. The solder particles may be aggregates of solder particles having these shapes.

[0079] The solder particles are preferably spherical. At this time, they are evenly dispersed inside the metal body and voids are generated inside the evenly dispersed solder or on the periphery of the solder (between the solder and the copper sintered body), thereby easily suppressing the volume shrinkage of the conductive via precursor described later during sintering and suppressing the disconnection generated in the conductive via portion.

[0080] When the total mass of the metal particles is 100 parts by mass, the content of the solder particles in the metal paste may be 0.3 to 15 parts by mass, 1 to 10 parts by mass, or 2 to 5 parts by mass.

[0081] Furthermore, the content of the solder particles may be 0.2 to 13 parts by mass, 0.8 to 9 parts by mass, or 1.5 to 4 parts by mass relative to 100 parts by mass of the total of the first copper particles and the second copper particles contained in the metal paste. If the content of the solder particles is within the above range, it is easy to form a conductive through hole while suppressing the generation of voids or cracks in the hole, and the conductive through hole has a porous structure and fully forms a conductive network.

[0082] The metal paste may contain metal particles other than copper particles and solder particles (hereinafter also referred to as "other metal particles"). Examples of other metal particles include nickel particles, silver particles, gold particles, palladium particles, and platinum particles. These may contain one or more kinds. The average particle size of other metal particles may be greater than 0.01 μm, greater than 0.03 μm, or greater than 0.05 μm, or less than 5 μm, less than 3.0 μm, or less than 2.0 μm. When the total mass of the metal particles is set to 100 parts by mass, the content of other metal particles may be less than 5 parts by mass, less than 3 parts by mass, or less than 1 part by mass. Other metal particles may also be excluded. The shape of other metal particles is not particularly limited.

[0083] Examples of the volatile solvent include monohydric alcohols and polyhydric alcohols such as pentanol, hexanol, heptanol, octanol, decanol, ethylene glycol, diethylene glycol, propylene glycol, butanediol (1,3-butanediol, etc.), α-terpineol, and isobornylcyclohexanol (MTPH); ethylene glycol butyl ether, ethylene glycol phenyl ether, diethylene glycol methyl ether, diethylene glycol ethyl ether (ethyl carbitol), diethylene glycol butyl ether (diethylene glycol mono-n-butyl ether, etc.), diethylene glycol isobutyl ether, diethylene glycol hexyl ether, triethylene glycol methyl ether, diethylene glycol dimethyl ether, diethylene glycol diethyl ether, diethylene glycol dibutyl ether, diethylene glycol butyl methyl ether, diethylene glycol isopropyl methyl ether, triethylene glycol dimethyl ether, triethylene glycol butyl methyl ether, propylene glycol propyl ether, dipropylene glycol methyl ether, dipropylene glycol ethyl ether, and dipropylene glycol. Ethers such as propyl ether, dipropylene glycol butyl ether, dipropylene glycol dimethyl ether, tripropylene glycol methyl ether, and tripropylene glycol dimethyl ether; esters such as dimethyl phthalate, ethylene glycol ethyl ether acetate, ethylene glycol butyl ether acetate, propylene glycol diacetate, diethylene glycol ethyl ether acetate, diethylene glycol butyl ether acetate, dipropylene glycol methyl ether acetate (DPMA), ethyl lactate, butyl lactate, γ-butyrolactone, and propylene carbonate; acid amides such as N-methyl-2-pyrrolidone, N,N-dimethylacetamide, and N,N-dimethylformamide; aliphatic hydrocarbons such as cyclohexane, octane, nonane, decane, and undecane; aromatic hydrocarbons such as benzene, toluene, and xylene; thiols having an alkyl group having 1 to 18 carbon atoms; and thiols having a cycloalkyl group having 5 to 7 carbon atoms. Examples of the mercaptan having an alkyl group having 1 to 18 carbon atoms include ethyl mercaptan, n-propyl mercaptan, isopropyl mercaptan, n-butyl mercaptan, isobutyl mercaptan, tert-butyl mercaptan, pentyl mercaptan, hexyl mercaptan, and dodecyl mercaptan. Examples of the mercaptan having a cycloalkyl group having 5 to 7 carbon atoms include cyclopentyl mercaptan, cyclohexyl mercaptan, and cycloheptyl mercaptan. The volatile solvent may be used alone or in combination of two or more.

[0084] From the viewpoint of printability and suppressing volume shrinkage before and after firing the conductive via precursor (for example, between the step of forming the conductive via precursor and the step of firing the conductive via precursor) to suppress voids or cracks, the metal paste may contain a solvent having a vapor pressure of 4 Pa ​​or more and 30 Pa or less at 20° C. (hereinafter also referred to as a “high vapor pressure solvent”) as a volatile solvent. One high vapor pressure solvent may be used alone or two or more high vapor pressure solvents may be used in combination.

[0085] Examples of the high vapor pressure solvent include α-terpineol, 1,3-butanediol, ethyl carbitol, and propylene glycol diacetate.

[0086] From the viewpoint of suppressing drying and powdering due to solvent volatilization during printing or paste preparation, the metal paste may contain a solvent having a vapor pressure of less than 4 Pa ​​at 20° C. (hereinafter also referred to as a “low vapor pressure solvent”) as a volatile solvent. The low vapor pressure solvent may be used alone or in combination of two or more.

[0087] Examples of the low vapor pressure solvent include isobornylcyclohexanol (MTPH), dimethyl phthalate, and diethylene glycol mono-n-butyl ether.

[0088] From the perspective of taking into account both printability and suppressing volume shrinkage before and after the conductive via precursor is fired (for example, between the process of forming the conductive via precursor and the process of firing the conductive via precursor) to suppress voids or cracks, the metal paste may contain a high vapor pressure solvent and a low vapor pressure solvent. At this time, the high vapor pressure solvent and the low vapor pressure solvent may be used alone or in combination of two or more. Regarding the content ratio of the high vapor pressure solvent and the low vapor pressure solvent, the mass ratio [high vapor pressure solvent / low vapor pressure solvent] may be 20 / 80 to 80 / 20, or 30 / 70 to 70 / 30.

[0089] The content of the volatile solvent in the metal paste may be 8 mass % or more, 7 mass % or more, or 6 mass % or less, or 1 mass % or less, 2 mass % or less, or 3 mass % or less, based on the total mass of the metal paste.

[0090] The metal paste may contain a resin component such as an epoxy resin. In the metal paste of this embodiment, the content of the resin component may be 10% by mass or less, or 5% by mass or less, or the metal paste may not contain the resin component.

[0091] The metal paste can be prepared by mixing the copper particles, solder particles and any components (additives, other metal particles, etc.) with the volatile solvent. The components can also be stirred after mixing. The maximum diameter of the dispersion can also be adjusted by classification.

[0092] In the case where the metal paste includes the first copper particles and the second particles, the second copper particles, the surface treatment agent, and the dispersion medium may be mixed in advance for dispersion treatment to prepare a dispersion of the second copper particles, and the first copper particles, solder particles, other metal particles as required, and any additives may be further mixed to prepare. By performing such a step, the dispersibility of the second copper particles is improved and the mixing property with the first copper particles becomes good, further improving the performance of the metal paste. Agglomerates may also be removed by providing the dispersion of the second copper particles to a classification operation.

[0093] From the viewpoint of printability, the viscosity of the metal paste at 25° C. may be 100 to 600 Pa·s or 150 to 400 Pa·s. The viscosity of the metal paste was measured using a micro-rotational viscometer PCU-02V (manufactured by Malcom Co., Ltd., product name) at a rotation speed of 10 rpm and a temperature of 25° C.

[0094] The composition of the metal particles and the volatile solvent in the metal particle-containing layer can be appropriately set in a manner that satisfies the conditions in the above-mentioned metal paste. The thickness of the metal particle-containing layer can be 100 μm or less. From the perspective of easily ensuring sufficient filling of the through hole or the non-through hole, the thickness of the metal particle-containing layer can be 30 μm or more, 40 μm or more, or 50 μm or more.

[0095] From the viewpoint of suppressing the generation of voids in through holes or non-through holes, the corrugation (height difference) on the surface of the metal particle-containing layer on the opposite side of the support film can be 20 μm or less, or 10 μm or less. By reducing the corrugation (height difference), when the metal particle film is pressed to fill the metal particle composition into the holes of the substrate, it is easy to fill multiple through holes or non-through holes on the substrate at the same time, and it is easy to reduce completely unfilled through holes or non-through holes, or through holes or non-through holes with partially generated voids. In addition, the evaluation of the corrugation (height difference) can be measured by a non-contact method using a laser displacement meter or the like.

[0096] The above-mentioned metal particle film can be produced by the following method: coating the metal paste of the above-mentioned embodiment on a support film to form a metal particle-containing layer with a metal particle concentration of more than 94 mass %, or by coating a metal paste obtained by increasing the content of volatile solvent in the metal paste (for example, increasing it to an amount where the concentration of metal particles is less than 92 mass %) and drying the coated film to form a metal particle-containing layer with a metal particle concentration of more than 94 mass %.

[0097] As a method for applying the metal paste, for example, there can be mentioned a method of applying using screen printing, transfer printing, offset printing, inkjet printing, a dispenser, a jet dispenser, a needle dispenser, a comma coater, a slit coater, a die coater, a gravure coater, a slit coating, relief printing, gravure printing, gravure printing, template printing, soft lithography, rod coating, applicator, particle accumulation method, spray coater, spin coater, dip coater, etc.

[0098] From the viewpoint of coating workability and uniformity of coating film thickness, the metal paste can be applied to the support film by screen printing.

[0099] The thickness of the coating film can be greater than 1 μm, greater than 2 μm, greater than 3 μm, greater than 5 μm, greater than 10 μm, greater than 15 μm or greater than 20 μm, or less than 300 μm, less than 250 μm, less than 200 μm, less than 150 μm, less than 120 μm, less than 100 μm, less than 80 μm or less than 50 μm.

[0100] The step of drying the coating film to form the metal particle-containing layer can be performed at room temperature or at a temperature from room temperature to 100° C. or lower, and the atmosphere may be air or nitrogen.

[0101] In step a, the metal particle film is pressed against the silicon substrate 40 so that the metal particle-containing layer 3p of the metal particle film is in contact with the silicon substrate 40, thereby filling the through hole 30 of the silicon substrate 40 with the metal paste. Figure 2 As shown in (b), a pressurizing fixture A can be used to clamp the metal particle film and the silicon substrate 40 from the top and bottom and apply pressure. The pressurizing fixture A is not particularly limited, and a commercially available product can be used, or it can be made using a metal component with a flat portion. For example, a pressurizing fixture having two or more of the above-mentioned metal components clamps the metal particle film and the silicon substrate between the metal components arranged in a manner such that the flat portions are opposed, thereby being able to press the metal particle film against the silicon substrate. The pressurizing fixture A may have a mechanism for adjusting the pressure applied to the metal particle film and the silicon substrate. As a pressure adjustment means, a spring or the like can be used.

[0102] Regarding the pressing conditions, for example, it can be carried out at a temperature below room temperature to 50°C, and regarding the atmosphere, it can be in a vacuum, in the atmosphere, or in nitrogen. In order to reduce the gap, the metal particle film can be pressed against the silicon substrate after maintaining a vacuum degree below 1000Pa or a vacuum degree below 200Pa. The pressure of the pressurizing fixture when pressing the metal particle film against the silicon substrate can be any pressure within a range where the silicon wafer will not break, for example, it can be above 0.01MPa, above 0.1MPa, or above 1MPa.

[0103] The metal paste portion 3 only needs to fill the inside of the hole and cover at least the surface of the periphery of the hole of the substrate. Figure 2 (b) and Figure 2 As shown in (c), the metal paste portion may also be formed from the opening of the through hole located on the side of the substrate opposite to the side on which the metal particle film is pressed ( Figure 2 The VP0 in (a) overflows and covers the surface around the hole.

[0104] [Process b]

[0105] In this process, the metal paste portion is heated to remove a portion of the volatile solvent, in other words, the metal paste portion is heated in a manner that a portion of the volatile solvent (e.g., the low vapor pressure solvent) remains. In addition, when the metal particle film is used, the metal paste portion can be heated after the support film is peeled off.

[0106] Regarding heating, for example, a hot plate, a hot air dryer, a hot air heating furnace, a nitrogen dryer, an infrared dryer, an infrared heating furnace, a far-infrared heating furnace, a microwave heating device, a laser heating device, an electromagnetic heating device, a heater heating device, a steam heating furnace, a hot plate pressing device, etc. can be used.

[0107] The heating atmosphere may be air, an oxygen-free atmosphere such as nitrogen and rare gas, or a reducing atmosphere such as hydrogen and formic acid. In the case of air, if the heating temperature exceeds 100°C, the copper particles are easily oxidized, but if the metal paste portion contains the above-mentioned high vapor pressure solvent as a volatile solvent, a portion of the volatile solvent can be removed at a temperature less than 100°C, below 95°C, or below 90°C. In addition, in the case where the metal paste portion does not contain a high vapor pressure solvent but, for example, only contains the above-mentioned low vapor pressure solvent as a volatile solvent, heating is performed in an oxygen-free atmosphere or in a reducing atmosphere at a temperature above 110°C, above 130°C, or above 150°C, so that oxidation of the copper particles can be suppressed while removing a portion of the volatile solvent.

[0108] When the metal paste portion contains a high vapor pressure solvent, from the viewpoint of suppressing the oxidation of the copper particles, the heating temperature can be above 70°C and below 100°C, or above 80°C and below 95°C. From the viewpoint of suppressing the oxidation of the copper particles, the heating time can be 5 to 60 minutes, or 10 to 30 minutes.

[0109] Furthermore, from the perspective of suppressing volume shrinkage before and after firing the conductive via precursor (for example, between the step of forming the conductive via precursor and the step of firing the conductive via precursor) to suppress voids or cracks, heating can be performed in such a manner that the concentration of metal particles in the metal paste portion becomes greater than 96 mass %, greater than 97.5 mass %, or greater than 98 mass %.

[0110] [Process c]

[0111] In this process, if Figure 3 (a)~ Figure 3 As shown in (d), for the heated metal paste portion 3a obtained in step b, the metal paste covering the surface of the substrate is removed and the metal paste filled in the hole is flattened (or smoothed). Thus, a conductive via precursor 3b ( ) having a flattened exposed surface VP1 and containing the remaining portion of metal particles and volatile solvent can be formed inside the hole (through hole 30). Figure 3 (d)).

[0112] Regarding the removal of the metal paste, for example Figure 3 (b) and Figure 3 As shown in (d), a rubber scraper 42 can be used. In this way, a part of the metal paste portion (the metal paste covering the surface of the substrate and the metal paste protruding from the hole) can be removed in such a way that the surface SP0 of the substrate 40 and the exposed surface VP1 of the conductive via precursor 3b become the same surface. In addition, as another method, a metal scraper such as SUS can be used for removal.

[0113] The height difference between the surface SP0 of the substrate 40 and the exposed surface VP1 of the conductive via precursor 3b may be 5 μm or less or 3 μm or less in the direction perpendicular to the substrate surface. The average height difference calculated by the following method may be within the above range.

[0114] (Average height difference)

[0115] An image of a cross section passing through the center of the hole (through hole) is obtained, and the cross-sectional image is binarized to obtain the cross-sectional area Sa enclosed by the inner wall of the hole (through hole), the exposed surface of the conductive through-hole precursor, and the opening surface of the hole (through hole), and the cross-sectional area Sa is divided by the spacing Wa of the inner wall of the hole to calculate the average height difference.

[0116] [Process d]

[0117] In this step, the conductive via precursor 3b formed in step c is fired, thereby forming a conductive via 3c formed of a metal body. The metal body can include a copper sintered body having a porous structure, solder dispersed in the copper sintered body, and pores.

[0118] Sintering can be performed by heat treatment. In the heat treatment, for example, heating means such as a hot plate, a hot air dryer, a hot air heating furnace, a nitrogen dryer, an infrared dryer, an infrared heating furnace, a far infrared heating furnace, a microwave heating device, a laser heating device, an electromagnetic heating device, a heater heating device, a steam heating furnace, etc. can be used.

[0119] From the viewpoint of suppressing the oxidation of the copper sintered body, the atmosphere during firing can be an oxygen-free atmosphere, and from the viewpoint of removing the surface oxide of the copper particles in the conductive via precursor, the atmosphere during firing can be a reducing atmosphere. As an oxygen-free atmosphere, for example, the introduction of oxygen-free gases such as nitrogen and rare gases or vacuum can be cited. As a reducing atmosphere, for example, pure hydrogen gas, a mixed gas of hydrogen and nitrogen represented by forming gas (Forming Gas), a nitrogen containing formic acid gas, a mixed gas of hydrogen and rare gases, a rare gas containing formic acid gas, etc. can be cited. In the case of heating in a non-pressurized state to sinter the conductive via precursor, it is preferably in pure hydrogen gas or a mixed gas of hydrogen and nitrogen represented by forming gas, preferably in pure hydrogen gas. By heating in pure hydrogen gas, the sintering temperature of the copper particles can be reduced. When pure hydrogen gas is used, even if the substrate thickness is as thick as 600 μm and the diameter of the through hole 30 is as small as 10 μm, the gas reaches the center of the through hole 30 , making it easy to obtain a metal body including a copper sintered body.

[0120] From the viewpoint of reducing thermal damage to each component and improving the yield rate, the maximum temperature reached during the heat treatment may be 150°C or more, or may be 350°C or less, 300°C or less, or 260°C or less. If the maximum temperature reached is 150°C or more, sintering tends to be fully performed when the maximum temperature is maintained for 60 minutes or less. From the viewpoint of volatilizing all volatile solvents and improving the yield rate, the maximum temperature maintenance time may be 1 minute or more, or may be 60 minutes or less, 40 minutes or less, or 30 minutes or less.

[0121] Regarding the sintering of the conductive through-hole precursor, it can be carried out in a non-pressurized state or in a state of applying pressure. In the case of being carried out in a state of applying pressure, in an atmosphere containing pure hydrogen gas, the pressure can be above 0.05MPa, above 0.1MPa, or above 0.3MPa, or below 20MPa, below 15MPa, or below 10MPa. In addition, in an atmosphere containing nitrogen, the pressure can be above 1MPa, above 3MPa, or below 20MPa, below 15MPa, or below 10MPa.

[0122] By setting the pressure to 0.05 MPa or more when pure hydrogen gas is used and setting the pressure to 1 MPa or more when nitrogen gas is used, it is easy to suppress the generation of voids in the conductive via formed in the central portion of the through hole 30, and it is easy to obtain a conductive via with good conductivity. In addition, by setting the pressure to more than the above lower limit, when the silicon substrate 40 has a metal film 2, it is easy to improve the bonding strength between the metal film 2 and the conductive via.

[0123] Furthermore, if the pressure during firing is within the above range, no special pressurizing device is required, so the yield rate will not be impaired, the gap can be reduced, and the bonding strength and connection reliability can be further improved. As a method of applying pressure to the silicon substrate forming the conductive through-hole precursor in the through-hole, for example, a method of placing a heavy object, a method of applying pressure using a pressurizing device, a method of applying pressure using a fixing fixture for pressurizing, etc. can be cited.

[0124] In the copper sintered body included in the metal body, the proportion of copper in the elements other than light elements in the constituent elements may be 95 mass % or more, 97 mass % or more, 98 mass % or more, or 100 mass %. If the above proportion of copper in the copper sintered body is within the above range, the formation of intermetallic compounds or the precipitation of heterogeneous elements to the metal copper grain boundaries can be suppressed, the properties of the metal copper constituting the copper sintered body are easy to become strong, and further excellent connection reliability is easy to obtain.

[0125] In step d, since the conductive via precursor has a flat exposed surface VP1 with a sufficiently small height difference from the substrate surface, and has a composition that is unlikely to shrink in volume by firing, the height difference between the surface SP0 of the substrate 40 and the exposed surface VP2 of the conductive via 3c can be sufficiently reduced. Thus, a substrate with conductive vias having sufficient flatness can be obtained, and a flattening step such as a CMP step can be omitted. In addition, in this embodiment, chemical polishing, mechanical polishing, chemical mechanical polishing, rapid cutting treatment, plasma treatment, and the like can also be performed as needed.

[0126] The height difference between the surface SP0 of the substrate 40 and the exposed surface VP2 of the conductive via 3c (or the depression of the conductive via 3c) in the direction perpendicular to the substrate surface can be 5 μm or less, or 3 μm or less. Furthermore, the average height difference calculated by the following method can be within the above range.

[0127] (Average height difference)

[0128] An image of a cross section passing through the center of the hole (through hole) is obtained, and the cross-sectional image is binarized to obtain the cross-sectional area Sb enclosed by the inner wall of the hole (through hole), the exposed surface of the conductive through hole, and the opening surface of the hole (through hole), and the cross-sectional area Sb is divided by the spacing Wb of the inner wall of the hole to calculate the average height difference.

[0129] After the above steps a to d, a substrate with conductive vias 50 can be obtained. Since the exposed surface of the conductive vias of the substrate 50 is flat (smooth) and has a sufficiently small height difference with the surface SP0 of the substrate 40, wiring can be easily formed, and even after the wiring is formed, a sufficiently low connection resistance value is shown.

[0130] <Method for manufacturing wiring board with conductive through-hole>

[0131] The method for manufacturing a wiring board with conductive vias according to the present embodiment includes a step of forming wiring on the board with conductive vias obtained by the above-mentioned method.

[0132] This process can include a resist forming process, a plating process, a resist removing process, and an etching process described below.

[0133] <Resist Formation Process>

[0134] In the resist forming process, for example, Figure 4 (a) and Figure 4 As shown in (b), after a negative photosensitive dry film 8 for etching resist is laminated on the main surface of the silicon substrate 40 and the conductive through hole 3c, a photomask that allows light to pass through in the shape of a wiring is overlapped, exposed with ultraviolet rays, and the unexposed parts are removed with a developer, thereby forming an etching resist 8a.

[0135] Examples of methods for forming the etching resist 8 a other than those described above include a method of screen printing an etching resist ink and a method of laminating a dry film resist using a laminator.

[0136] <Plating process>

[0137] In the plating process, for example Figure 4 As shown in (c), the wiring 9 can be formed in the opening of the resist 8a by a method such as electrolytic plating or electroless plating.

[0138] <Resist Removal Process>

[0139] In the resist removal process, for example Figure 4 As shown in (d), the resist 8a can be removed by wet stripping using an organic solvent solution such as an alkaline aqueous solution or an organic amine such as TMAH or a ketone such as acetone, or dry stripping using plasma or ozone.

[0140] <Etching process>

[0141] In the etching step, the metal film 2 of the portion not covered by the wiring 9 can be removed by etching. In the present embodiment, a portion of the metal film 2 provided on both main surfaces of the silicon wafer 1 is removed by etching.

[0142] Examples of the etching method include methods using chemical etching solutions commonly used for wiring boards, such as a solution of cuprous chloride and hydrochloric acid, a solution of ferrous chloride, a solution of sulfuric acid and hydrogen peroxide, and an ammonium persulfate solution.

[0143] Through the above process, it is possible to obtain Figure 4 (e) A wiring substrate 52 with conductive vias as shown.

[0144] In the method for manufacturing a wiring substrate with conductive vias of this embodiment, the substrate with conductive vias having wiring formed thereon may be subjected to a process for removing at least a portion of a conductor such as a sintered body of metal paste or metal film 2 remaining on the main surface of silicon substrate 40 .

[0145] As a means of removing the conductor, there are chemical polishing, mechanical polishing, chemical mechanical polishing, fly-cut processing, plasma processing, etc. The fly-cut processing means cutting and flattening by a surface planer.

[0146] Example

[0147] Hereinafter, the present invention will be described in more detail with reference to Examples and Comparative Examples, but the present invention is not limited to the following Examples.

[0148] [Preparation of Metal Paste]

[0149] (Preparation Example 1 to Preparation Example 24)

[0150] The following raw materials were mixed at the ratios shown in Tables 1 to 3 to prepare metal pastes.

[0151] <First copper particle>

[0152] (Wet copper powder)

[0153] Spherical copper particles W1: 1050Y (manufactured by Mitsui Mining & Smelting Co., Ltd., product name, average particle size (D50): 0.81 μm, spherical)

[0154] Spherical copper particles W2: 1100Y (manufactured by Mitsui Mining & Smelting Co., Ltd., product name, average particle size (D50): 1.1 μm, spherical)

[0155] Spherical copper particles W3: 1200Y (manufactured by Mitsui Mining & Smelting Co., Ltd., product name, average particle size (D50): 2.1 μm, spherical)

[0156] Spherical copper particles W4: 1300Y (manufactured by Mitsui Mining & Smelting Co., Ltd., product name, average particle size (D50): 3.5 μm, spherical)

[0157] Flat copper particles W1: 1100YP (manufactured by Mitsui Mining & Smelting Co., Ltd., product name, average particle size (D50): 1.4 μm, flat)

[0158] Flat copper particles W2: 1200YP (manufactured by Mitsui Mining & Smelting Co., Ltd., product name, average particle size (D50): 3.1 μm, flat)

[0159] (Atomized copper powder)

[0160] Spherical copper particles A1: MA-C02K (manufactured by Mitsui Mining & Smelting Co., Ltd., product name, average particle size (D50): 1.8 μm, spherical)

[0161] Spherical copper particles A2: MA-C025K (manufactured by Mitsui Mining & Smelting Co., Ltd., product name, average particle size (D50): 2.4 μm, spherical)

[0162] Spherical copper particles A3: MA-C03K (manufactured by Mitsui Mining & Smelting Co., Ltd., product name, average particle size (D50): 3.4 μm, spherical)

[0163] <Second copper particle>

[0164] Spherical copper particles W5: CH0200L1 (manufactured by Mitsui Mining & Smelting Co., Ltd., product name, average particle size (D50): 200 nm, spherical)

[0165] <Solder particles>

[0166] Solder particles 1: SnBi58 solder STC-3 (manufactured by Mitsui Mining & Smelting Co., Ltd., product name, average particle size (D50): 4.1 μm, spherical)

[0167] <Volatile Solvent>

[0168] (High vapor pressure solvent: vapor pressure at 20°C is 4 Pa ​​or more and 30 Pa or less)

[0169] α-Terpineol: manufactured by FUJIFILM Wako Pure Chemical Corporation. Vapor pressure at 20°C: 6.5 Pa

[0170] 1,3-Butanediol: Made by SANKYO CHEMICAL Co., Ltd., vapor pressure at 20°C: 8 Pa

[0171] Ethyl carbitol: manufactured by Showa Chemical Industry Co., Ltd., vapor pressure at 20°C: 13 Pa

[0172] Propylene glycol diacetate: manufactured by INOUE PERFUMERY MFG.CO.,LTD., vapor pressure at 20°C: 30 Pa

[0173] (Low vapor pressure solvent: vapor pressure at 20°C is less than 4Pa)

[0174] Isobornyl cyclohexanol: manufactured by NIPPON TERPENE CHEMICALS, INC., product name "Tersorb MTPH", vapor pressure at 20°C: 0.004 Pa

[0175] Dimethyl phthalate: manufactured by Showa Chemical Industry Co., Ltd., vapor pressure at 20°C: 0.2 Pa

[0176] Diethylene glycol mono-n-butyl ether: manufactured by Showa Chemical Industry Co., Ltd., vapor pressure at 20°C: 1.3 Pa

[0177] The metal pastes obtained in Preparation Examples 1 to 24 were evaluated for viscosity, printability, bonding properties, and volume resistivity according to the following methods.

[0178] <Viscosity>

[0179] The viscosity of the metal paste was measured using a micro-rotational viscometer PCU-02V (manufactured by Malcom Co., Ltd., product name) The measurement conditions were a rotation speed of 10 rpm and a temperature of 25°C.

[0180] <Printability>

[0181] The number of pinholes that could not be applied to the PET film side when printing was performed on a 100 μm thick PET film using a screen printer in the later-described <Preparation of Metal Particle Film> was measured. The printability was evaluated according to the following criteria based on the number of pinholes. In addition, the evaluations A to D were judged to be good.

[0182] (Judgment Criteria)

[0183] A: The number of pinholes is 0

[0184] B: The number of pinholes is 1 or more and less than 3

[0185] C: The number of pinholes is 3 or more and less than 5

[0186] D: The number of pinholes is 5 or more and less than 10

[0187] E: The number of pinholes is more than 10 and less than 20

[0188] F: The number of pinholes is more than 20

[0189] In addition, the 8-inch film was printed on a 100 μm thick PET film using a screen printer in the <Preparation of Metal Particle Film> described later. Size Coating Amount (g).

[0190] <Joinability>

[0191] The preparation of the bonded sample for the shear strength test and the measurement of the wafer shear strength were performed in the following manner, and the bondability was evaluated in accordance with the following criteria: The samples evaluated as A to C were judged to be good.

[0192] (Preparation of joint samples for shear strength test)

[0193] Use a 3×3mm 2A stainless steel mask with a square opening and a thickness of 100 μm and a scraper are used to print the metal paste template on a copper plate with a size of 25×20×3 mm in thickness. After drying at 90°C for 10 minutes using a hot plate, it is placed in a tubular furnace (manufactured by AVC Co., LTD.), and argon is allowed to flow at a flow rate of 1 L / min to replace the air in the tubular furnace with argon. Then, while hydrogen is allowed to flow at 300 mL / min, the temperature is raised to 225°C within 10 minutes, and a sintering treatment is performed at 225°C for 60 minutes to sinter the metal paste. Then, argon is allowed to flow at a flow rate of 0.3 L / min and cooled, and taken out into the air at a temperature below 50°C, thereby obtaining a substrate with a metal body formed on the copper plate as a bonding sample for a shear strength test.

[0194] (Determination of wafer shear strength)

[0195] For the bonded sample for shear strength test, a universal bond tester (4000 series, manufactured by DAGE) equipped with a DS-100 load cell was used to press the metal body or Cu plate in the horizontal direction under the measurement conditions of measurement speed: 5 mm / min and measurement height: 50 μm, and the wafer shear strength was measured. The average value of 10 locations was calculated and used as the average value of the bond strength.

[0196] (Judgment Criteria)

[0197] A: The average bonding strength is 50N or more

[0198] B: The average bonding strength is 40N or more and less than 50N

[0199] C: The average bonding strength is 20N or more and less than 40N

[0200] D: The average bonding strength is 10N or more and less than 20N

[0201] E: The average value of the bonding strength is less than 10N

[0202] <Measurement of volume resistivity>

[0203] Using an automatic coating machine (manufactured by ALLGOOD, product name), the metal paste prepared above is coated on a glass wafer with a thickness of 1 mm so that the coating thickness is about 150 μm. In addition, the coating area is set to about 5 cm × about 10 cm. Next, using a hot plate, the wafer provided with the coating film is dried at 90 ° C for 10 minutes, and then placed in a tubular furnace (manufactured by AVC Co., LTD.), and argon is flowed at 1 L / min to replace the air in the tubular furnace with argon. Then, while hydrogen is flowed at 300 mL / min, the temperature is raised to 225 ° C within 10 minutes, and a sintering treatment is performed at 225 ° C for 60 minutes to sinter the metal paste. Then, argon is flowed at a flow rate of 0.3 L / min and cooled, and taken out into the air at a temperature below 50 ° C, thereby obtaining a sample having a metal body formed on the wafer.

[0204] The volume resistivity of the metal body in the sample was calculated from the surface resistance value measured using a four-probe surface resistance meter (manufactured by Mitsubishi Chemical Analytech Co., Ltd., product name: Loresta GP) and the film thickness determined using a non-contact surface-layer cross-sectional shape measurement system (VertScan, Ryoka Systems Inc.).

[0205]

[0206]

[0207]

[0208] [Fabrication of Silicon Substrate with Conductive Vias]

[0209] (Example 1 to Example 24)

[0210] A silicon substrate with conductive through-holes was fabricated according to the following steps.

[0211] <Preparation of silicon substrate>

[0212] A silicon substrate having a through hole and having titanium layers, nickel layers, and copper layers formed in sequence on two main surfaces and the wall surface of the through hole was prepared. In addition, the silicon substrate had a diameter of 6 inches and a thickness of 300 μm, and the titanium layer, nickel layer, and copper layer were formed in sequence by sputtering, and the aperture (through hole diameter) of the through hole was 30 μm.

[0213] <Preparation of Metal Particle Film>

[0214] Using a screen printer and a screen printing plate (wire diameter: 23 μm, mesh number: 400, pore size: 41 μm, porosity: 41 μm), the metal paste prepared above was printed on a PET film with a thickness of 100 μm at an 8-inch The printing was performed on a circle with a size of 20 cm in diameter, thereby obtaining a metal particle film provided with a metal particle-containing layer.

[0215] <Formation of conductive vias>

[0216] The metal particle film was laminated to the silicon substrate from the metal particle layer side using a laminating device VJ-35 (manufactured by Ayumi Industry Co., Ltd., product name), and the laminate was further pressed at room temperature, in the atmosphere, and under a pressure of 3 MPa to fill the through-holes with the metal paste. At this time, the metal paste was made to protrude on the side of the silicon substrate opposite to the side where the metal particle film was laminated.

[0217] Next, the article after the PET film was peeled off from the above-mentioned laminate was dried in air at 90° C. for 10 minutes. In addition, only Examples 18 and 19 were dried at 130° C. in a nitrogen atmosphere (flow rate 5 L / min) for 60 minutes. These drying conditions changed the concentration of metal particles in the metal paste as follows.

[0218] Examples 1 to 15, Examples 20 to 22: 95 mass % → 97.5 mass %

[0219] Example 16: 95 mass% → 99.5 mass%

[0220] Example 17: 95 mass% → 99 mass%

[0221] Example 18: 95 mass% → 98.4 mass%

[0222] Example 19: 95 mass% → 97.6 mass%

[0223] Example 23: 95 mass% → 98.2 mass%

[0224] Example 24: 95 mass% → 98.5 mass%

[0225] Regarding the dried laminate, Figure 3 (a)~ Figure 3 As shown in (d), the metal paste on the main surface of the silicon substrate on which the metal particle film is bonded is removed using a rubber scraper, and then the metal paste protruding on the side of the silicon substrate opposite to the side on which the metal particle film is bonded is removed using a rubber scraper.

[0226] Next, the silicon substrate in which the conductive through-hole precursor is formed in the through-hole by the above process is placed in a tube furnace (manufactured by AVC Co., LTD.), and argon gas is flowed at 1 L / min to replace the air in the tube furnace with argon gas. Then, while hydrogen gas is flowed at 300 mL / min, the temperature is raised to 225°C within 10 minutes, and a sintering treatment is performed at 225°C for 60 minutes to sinter the conductive through-hole precursor. Then, argon gas is flowed at a flow rate of 0.3 L / min and cooled, and taken out into the air at a temperature below 50°C, thereby obtaining a silicon substrate with a conductive through-hole.

[0227] <Evaluation of Silicon Substrates with Conductive Vias>

[0228] The silicon substrate with conductive vias obtained above was evaluated for the presence or absence of cracks and voids in the conductive vias and for depressions after sintering by the following method.

[0229] (Presence or absence of cracks in conductive vias)

[0230] The cross-section of the conductive via of the silicon substrate with the conductive via was exposed by cross-section grinding, and 30 conductive vias were observed using a digital microscope (manufactured by KEYENCE CORPORATION, product name: VHX-6000) to confirm the presence or absence of cracks (length of 10 μm or more).

[0231] (Presence or absence of voids in conductive vias)

[0232] The cross-section of the conductive via of the silicon substrate with the conductive via was exposed by cross-section polishing, and 30 conductive vias were observed using a digital microscope (manufactured by KEYENCE CORPORATION, product name: VHX-6000) to confirm the presence or absence of voids (diameter of 5 μm or more).

[0233] (Depression after sintering)

[0234] The cross section of the conductive via of the silicon substrate with the conductive via was exposed by cross-sectional grinding, 30 conductive vias were observed using a digital microscope (manufactured by KEYENCE CORPORATION, product name: VHX-6000), and the average height difference was calculated by the following method.

[0235] [Average height difference]

[0236] An image of a cross section passing through the center of the through hole is obtained and binarized to obtain the cross-sectional area Sb surrounded by the inner wall of the through hole, the exposed surface of the conductive through hole and the opening surface of the through hole, and the cross-sectional area Sb is divided by the spacing Wb of the inner wall of the hole to calculate the average height difference (= Sb / Wb).

[0237] The average value of the average height difference of 30 locations was calculated, and the depression after sintering was evaluated according to the following criteria: An evaluation of C or higher can be judged as good.

[0238] (Judgment Criteria)

[0239] A: The average height difference is less than 1μm

[0240] B: The average height difference is 1 μm or more and less than 3 μm

[0241] C: The average height difference is 3 μm or more and less than 5 μm

[0242] D: The average height difference is 5 μm or more and less than 10 μm

[0243] E: The average height difference is more than 10μm

[0244] <Evaluation of wiring boards>

[0245] Using a laminator, a UV curable resist dry film H-W425 (product name, manufactured by Resonac Corporation) was pressed onto the surface of the silicon substrate with conductive through holes obtained above. After that, the wiring pattern was exposed to a photomask and the resist was developed. Next, after electrolytic plating was performed on the resist opening, the resist was stripped and the seed layer was etched to form a wiring pattern of 300μm×600μm, thereby obtaining a wiring pattern as shown in FIG. Figure 5 Test piece 55 (wiring board) as shown. In test piece 55, the conductive vias formed in the through holes are electrically connected via wiring provided on the surface of the board.

[0246] The test pieces obtained above were evaluated for initial resistance value, connection reliability, presence or absence of cracks in the substrate, and depression of the conductive via after resist peeling according to the following methods.

[0247] (Initial resistance value)

[0248] The resistance values ​​of 30 through-hole connections were measured as the initial resistance value of the test piece 55. Based on the connection resistance values, the initial resistance value was evaluated according to the following criteria. An evaluation of B or higher can be judged as good.

[0249] (Judgment Criteria)

[0250] A: Resistance value is less than 10mΩ

[0251] B: Resistance value is 10mΩ or more and less than 30mΩ

[0252] C: Resistance value is 30mΩ or more and less than 100mΩ

[0253] D: Resistance value is 100mΩ or more and less than 500mΩ

[0254] E: Resistance value is 500mΩ or more

[0255] (Connection reliability)

[0256] The test piece 55 was placed in a temperature cycle tester (TSA-72SE-W, manufactured by ESPEC CORP.) and a temperature cycle connection reliability test was performed under the conditions of low temperature side: -40°C, 15 minutes, room temperature: 2 minutes, high temperature side: 125°C, 15 minutes, defrost cycle: automatic, number of cycles: 50, 100, 300, 500 cycles. For the test piece that passed each number of cycles, the resistance value of 30 through-hole connections was measured. Based on the connection resistance value, the connection reliability was evaluated according to the following judgment criteria.

[0257] (Judgment Criteria)

[0258] A: Resistance change rate relative to the initial resistance value is less than 1%

[0259] B: The resistance change rate is 1% or more and less than 3% relative to the initial resistance value

[0260] C: The resistance change rate is 3% or more and less than 5% relative to the initial resistance value

[0261] D: The resistance change rate is 5% or more and less than 10% relative to the initial resistance value

[0262] E: The resistance change rate is 10% or more and less than 20% relative to the initial resistance value

[0263] F: Resistance change rate relative to the initial resistance value is more than 20%

[0264] (Crack of substrate)

[0265] The test piece 55 was visually inspected to check whether the silicon substrate had cracks.

[0266] (Depression after resist stripping)

[0267] In the preparation of the test piece 55, after the resist was stripped, the cross section of the conductive via was exposed by cross-section grinding, and 30 conductive vias were observed using a digital microscope (Keyence Corporation, product name: VHX-6000), and the average value of the average height difference was calculated by the same method as the evaluation of the depression after sintering. Then, the depression after the resist was stripped was evaluated according to the following judgment criteria. In addition, it can be judged that the evaluation of C or above is good.

[0268] (Judgment Criteria)

[0269] A: The average height difference is less than 1μm

[0270] B: The average height difference is 1 μm or more and less than 3 μm

[0271] C: The average height difference is 3 μm or more and less than 5 μm

[0272] D: The average height difference is 5 μm or more and less than 10 μm

[0273] E: The average height difference is more than 10μm

[0274] [Observation and investigation of conductive vias]

[0275] (Observation 1)

[0276] The silicon substrate with conductive vias produced in Example 1 was subjected to cross-sectional polishing to expose the cross section of the conductive vias, and a cross-sectional image was taken using a digital microscope (manufactured by KEYENCE CORPORATION, product name: VHX-6000) (reference Figure 6 ).like Figure 6 As shown, the conductive via includes a copper sintered body, solder 25 and a void 4, and the void exists in the copper sintered body, inside the solder, and the periphery of the solder (between the solder and the copper sintered body).

[0277] (Observation 2)

[0278] A focused ion beam processing observation device (manufactured by Hitachi High-Technologies Corporation, product name: MI4050) was used to expose the cross section of the central part of the conductive via of the silicon substrate with the conductive via by a focused ion beam, and the cross section was observed. During the observation, a scanning electron microscope (manufactured by Hitachi High-Technologies Corporation, product name: S-3700N) was used with a magnification of 10,000 times to take a cross-sectional image (about 10 μm square) of the copper sintered body (reference Figure 7 ).like Figure 7 As shown in (a), the copper sintered body has a structure in which the first copper particles 10 are distributed in the second copper particles 20. Figure 7As confirmed in the enlarged view of the cross-sectional image shown in (b), the wet copper powder 12 in the first copper particle has the characteristic of being easier to bond with the second copper particle than the atomized copper powder 14, but the connection reliability can be further improved by using the wet copper powder and the atomized copper powder together. It is believed that this effect is because the wet copper powder 12 that is easy to bond with the second copper particle and the atomized copper powder 14 with a wide particle size distribution coexist, and the wet copper powder 12 bonds the atomized copper powder 14 with each other and also with the second copper particle, thereby highly achieving the formation of a strong sintered body through the closest packing structure, suppressing the shrinkage during sintering to suppress the generation of voids or cracks, and suppressing depressions.

[0279]

[0280]

[0281]

[0282] As shown in Tables 4 to 6, it can be seen that according to the method of the embodiment, the height difference between the exposed surface of the conductive via after sintering and the substrate surface can be sufficiently reduced, and a substrate with conductive vias having sufficient flatness can be easily obtained. In addition, it can be seen that according to the method of the embodiment, a wiring substrate with conductive vias having wiring well connected through the conductive vias can be easily obtained.

[0283] Explanation of symbols

[0284] 1-silicon wafer, 2-metal film, 3-metal paste portion, 3b-conductive through hole precursor, 3c-conductive through hole, 3p-metal particle-containing layer, 7-support film, 8a-anti-etching resist, 9-wiring, 30-through hole, 31-non-through hole, 40, 41-silicon substrate, 42-rubber scraper, 50-substrate with conductive through holes, 52-wiring substrate with conductive through holes, 55-test piece, A-pressing fixture.

Claims

1. A method for manufacturing a substrate with conductive through holes, comprising: Step a, preparing a substrate having a hole, and providing a metal paste portion containing metal particles and a volatile solvent so as to fill the inside of the hole and cover at least the surface of the substrate around the hole; Step b: heating the metal paste portion to remove a portion of the volatile solvent; Step c: removing a portion of the heated metal paste portion so as to expose the surface, thereby forming a conductive via precursor having a planarized exposed surface and containing the metal particles and the remaining portion of the volatile solvent within the hole; and Step d: sintering the conductive via precursor.

2. The method according to claim 1, wherein The concentration of the metal particles in the metal paste portion provided in step a is 94% by mass or more, In the step b, the metal paste portion is heated so that the concentration of the metal particles becomes 97.5% by mass or more.

3. The method according to claim 1, wherein The volatile solvent includes a high vapor pressure solvent having a vapor pressure of 4 Pa ​​or more and 30 Pa or less at 20° C., The heating temperature in the step b is less than 100°C.

4. The method according to claim 1, wherein In the step a, a metal particle film including a support film and a metal particle-containing layer provided on the support film and containing the metal particles and the volatile solvent is prepared, and the metal particle-containing layer of the metal particle film is pressed against the substrate to provide the metal paste portion. 5 . A method for manufacturing a wiring board with conductive through holes, comprising the step of forming wiring on the board with conductive through holes obtained by the method according to claim 1 .